Incidencias de las pérdidas esperadas en la cartera de crédito de las Cooperativas de Ahorro y Crédito - Regalado Lozano, Giovanna Nathaly (2019)
The implementation of the International Financial Reporting Standards (IFRS) in the accounting of Ecuadorian entities brought about substantial improvements in the presentation of the financial reality of each entity, contributing significantly in the decision making of the users of the financial information, such as: investors, banking institutions, among others. However, these accounting changes, which mainly included more reliable valuations and estimates, were not adopted by certain economic sectors of Ecuador, which were not part of the aforementioned implementation, as was the national financial sector, represented by the Superintendencia de Bancos (SB) and the Superintendencia de Economía Popular y Solidaria (SEPS); This is because these state agencies maintained their own accounting policies or guidelines that contributed in a certain way, with a reasonable presentation of the financial statements of those institutions under their regulation, such as banks, savings and credit cooperatives, mutualists, among others……...